Las políticas socioambientales en los asentamientos humanos de rango medio - Galilea, Sergio; Jordán, Ricardo (Revista EURE - Revista de Estudios Urbano Regionales, 1984)
Galilea and Jordan raise the issue of the importance of introducing, with a high priority, the issue of the role of medium size human settlements as a policy option in the discussions about territorial and socioeconomic development. The main features medium size settlements have regarding costs and infrastructure allow for the hypothesis that they could play an increasingly major role as a target for alternative urban and regional development policies. Thus, the article concentrates in the methodological problems involved in incorporating the environmental variables in development plans. Closing the article, the authors pose a series of specific recommendations regarding the sectors involved.